2019
DOI: 10.1111/tbed.13269
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography, phylodynamics and the recent outbreak of lineage 3 porcine reproductive and respiratory syndrome viruses in China

Abstract: Novel highly pathogenic porcine reproductive and respiratory syndrome viruses (PRRSVs) have attracted increasing attention owing to their continual high emergence and recent re‐emergence. Recently, lineage 3 PRRSVs, belonging to the type 2 viruses, with novel characteristics and increased virulence have been continuously re‐emerging in China, thereby posing a great threat to pig farming. However, available information about lineage 3 is limited. Here, we carried out molecular epidemiological investigations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…After the two HP-PRRSV outbreaks, molecular epidemiology of PRRSV2 in China was complicated by the emergence of various novel PRRSV2 strains, possibly due to multiple introductions, including 1) the emergence of the NAD30-like viruses (lineage 1) in 2012 [27], 2) the emergence of the NADC34-like viruses (lineage 1) in 2018 [14,28] and 3) the diversified genetics of the lineage 3 viruses [29]. The presence of these novel PRRSVs in Asian countries requires further studies.…”
Section: Prrsvmentioning
confidence: 99%
“…After the two HP-PRRSV outbreaks, molecular epidemiology of PRRSV2 in China was complicated by the emergence of various novel PRRSV2 strains, possibly due to multiple introductions, including 1) the emergence of the NAD30-like viruses (lineage 1) in 2012 [27], 2) the emergence of the NADC34-like viruses (lineage 1) in 2018 [14,28] and 3) the diversified genetics of the lineage 3 viruses [29]. The presence of these novel PRRSVs in Asian countries requires further studies.…”
Section: Prrsvmentioning
confidence: 99%
“…A recent algorithm implemented in the TempEst software enables the exploration of the degree and pattern of the temporal signal in the datasets [ 41 ]. This approach has been successfully applied to guarantee a closer relationship between genetic information and the temporal pattern [ 42 , 43 ]. In the current study, the data obtained from the mgc2 marker showed a linear correlation between genetic distance and temporal structure, with an R 2 = 0.95 ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, a novel NADC30‐like PRRSV named JL580 emerged in northeast of China and lineage 1 rapidly spread throughout China (Bian et al, ; Li, Zhuang, et al, ; Wang et al, ; Zhao et al, ). Reemergence of lineage 3 was reported in 2010 in mainland China and became epidemic since then (Dong et al, ; Han, Xu, Wang, & He, ; Lu et al, ; Shi et al, ; Sun, Han, et al, ; Sun, Li, et al, ; Zhang et al, ). Lineage 8 is further categorized into sublineages 8.3–8.7 (HP‐PRRSV related), sublineage 8.1 (CH‐1a related) and sublineage 8.2 (Gao et al, ).…”
Section: Discussionmentioning
confidence: 99%